Development of an emperical model for dust storm attenuation prediction - Elsheikh, Elfatih A. A.; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi; Eltahir, E.I; Suliman, F.M. (2019)
This paper proposes an specific sand and dust storm fade estimation model. The proposed model is based on an empirical assessment of the impacts of the dust and sand storms on a terrestrial link operating at 21 GHz. The developed model is simple and reliable with minimum number of input parameters. Validation of the model with measurements at frequency range 14 GHz to 40 GHz showed close agreement.